Acute exacerbation of chronic disseminated intravascular coagulation associated with thoracoabdominal aortic aneurysm after tooth extraction. (2nd August 2017) - Hino, Shunsuke; Takeda, Akio; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract : Objective: To present a rare case of persistent bleeding from the tooth extraction socket in a patient with chronic disseminated intravascular coagulation (DIC). Background: Acute exacerbation of chronic DIC occurs by various trigger factors. Clinical report: The patient's chronic DIC in association with thoracoabdominal aortic aneurysm was activated by tooth extraction, resulting in persistent bleeding from the socket. Conclusion: Patients with chronic DIC may have persistent bleeding following tooth extraction.